2015
DOI: 10.1007/s10995-015-1763-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Preterm Birth Among Women Screened by North Carolina’s Pregnancy Medical Home Program

Abstract: Objective To determine which combination of risk factors from Community Care of North Carolina’s (CCNC) Pregnancy Medical Home (PMH) risk screening form was most predictive of preterm birth (PTB) by parity and race/ethnicity. Methods This retrospective cohort included pregnant Medicaid patients screened by the PMH program before 24 weeks gestation who delivered a live birth in North Carolina between September 2011-September 2012 (N=15,428). Data came from CCNC’s Case Management Information System, Medicaid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
0
38
1
Order By: Relevance
“…During the pregnancy, risk factors can be identified and managed. Chronic hypertension is one important risk factor for both PTB 18 and SGA, 19 20 and also for pre-eclampsia, 21 which can give rise to PTB–SGA. 22 Chronic hypertension is highly prevalent among Filipino women in Ontario 7 ; therefore, efforts to regulate blood pressure and prevent pre-eclampsia may help reduce the risk of PTB–SGA among Filipino women and also those from Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…During the pregnancy, risk factors can be identified and managed. Chronic hypertension is one important risk factor for both PTB 18 and SGA, 19 20 and also for pre-eclampsia, 21 which can give rise to PTB–SGA. 22 Chronic hypertension is highly prevalent among Filipino women in Ontario 7 ; therefore, efforts to regulate blood pressure and prevent pre-eclampsia may help reduce the risk of PTB–SGA among Filipino women and also those from Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies explored the association between FIS and children's anthropometric measurements (Table 4). Several manuscripts showed that there was no significant association between FIS and children's height (128), weight-for-length (70,146), weight-for-age (62,78), and probability of pre-term birth (147). Although one study did find an association between proxy-reported low birth weight and FIS(51).…”
Section: Children Anthropometric Measurementsmentioning
confidence: 99%
“…There have been numerous studies examining the potential mediating effect of many individual level social determinants of health presented in Table 1 on this differential risk of PTB. These individual level factors include receipt of welfare as a proxy for income (18); marital status and education level (19,20); exposure to racism and racial discrimination (21)(22)(23)(24)(25); and housing insecurity (26). In each case, inclusion of these factors individually explained some, but not all, of the observed disparities in PTB rates.…”
Section: Individual Factorsmentioning
confidence: 99%